UJI FITOKIMIA DAN UJI TOKSISITAS EKSTRAK DAUN GAMAL (Gliricidia sepium) SEBAGAI INSEKTISIDA NABATI - Ajeng Kartini; Daniel Daniel; Chairul Saleh (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2017)
Research on phytochemical test and toxicity tests of leaf extract of Gliricidia (Gliricidia sepium) as an insecticide plant have been conducted.. Gliricidia leaves macerated dried samples using ethanol and fractionated using a solvent n-hexane and ethyl acetate. Phytochemical test showed that it contains alkaloids, steroids, triterpenoids, phenolic and flavonoid in total extract. N-hexane fraction containing steroids, triterpenoids and the phenolic. Ethyl acetate fraction containing steroids, triterpenoids, flavonoids, phenolic and saponin. Toxicity test method Brine Shrimp Lethality Test (BSLT) showed that the ethyl acetate fraction had the highest toxicity on shrimp larvae with LC50 values ​​of 49.29 ppm. Test Activity as an insecticide plant conducted in animal infestation of rice (Sitophylusorizae Leach) Value LC50 is determined using a regression line between log concentration and probit mortality, the LC50 obtained is 2.831%. Analysis of the content of chemical compounds in the ethyl acetate fraction from the leaves of Gliricidia produces 9 peak component compounds at mass spectra are shown from the results of GC-MS with 2 peaks compound dominant that serves as an insecticide plant them 2-(3H)-Benzofuranone, 3-methyl and dl-Limonene